1984
DOI: 10.1017/s0022029900023517
|View full text |Cite
|
Sign up to set email alerts
|

Studies on micellar calcium phosphate: composition and apparent solubility product in milk over a wide pH range

Abstract: Calcium and phosphate concentrations in milk ultrafiltrate prepared at 37 °C over the pH range 4-0-8 -0 have been measured and used to calculate the apparent solubility products for various calcium phosphates in milk. Micellar calcium phosphate had a constant Ca/Pj = 158±003 at all pH values and a near-invariant ion activity product for CaHP0 4 . Apparent solubility products have also been obtained for brushite, hydroxyapatite and amorphous tricalcium phosphate in milk salt solution over a similar pH range. No… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
1
1

Year Published

1992
1992
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(30 citation statements)
references
References 10 publications
(13 reference statements)
3
25
1
1
Order By: Relevance
“…These results suggest that, whatever the added calcium concentration, the colloidal calcium phosphate of calcium-enriched milks contains some dicalcium phosphate-like materials in near-equilibrium with the serum, like nonenriched milk. Such a hypothesis is in good accordance with Holt [16][17][18] and Chaplin [6] who found that colloidal calcium phosphate of skim milk closely resembled brushite. In the same way, acidification of calcium-supplemented milks showed the same solubilization of colloidal calcium phosphate as that observed for reference milk: the same linear relationship between colloidal calcium and colloidal inorganic phosphate was obtained (1.73x ± 5.01, Fig.…”
Section: Influence Of Calcium Addition On the Behaviour Of Colloidal supporting
confidence: 86%
See 1 more Smart Citation
“…These results suggest that, whatever the added calcium concentration, the colloidal calcium phosphate of calcium-enriched milks contains some dicalcium phosphate-like materials in near-equilibrium with the serum, like nonenriched milk. Such a hypothesis is in good accordance with Holt [16][17][18] and Chaplin [6] who found that colloidal calcium phosphate of skim milk closely resembled brushite. In the same way, acidification of calcium-supplemented milks showed the same solubilization of colloidal calcium phosphate as that observed for reference milk: the same linear relationship between colloidal calcium and colloidal inorganic phosphate was obtained (1.73x ± 5.01, Fig.…”
Section: Influence Of Calcium Addition On the Behaviour Of Colloidal supporting
confidence: 86%
“…Relations between colloidal calcium concentration and colloidal inorganic phosphate concentration in the pH range 6.7-5.4 were also [19]. From the activities, and in the pH range 6.7-5.4, the ion activity products for dicalcium phosphate (CaHPO 4 ·2H 2 O and Ca(HPO 4 ) 0.7 (PO 4 ) 0.2 ) and tricalcium phosphate (Ca 3 (PO 4 ) 2 ) were calculated [6,19].…”
Section: Study Of the Behaviour Of Colloidal Calcium Phosphatementioning
confidence: 99%
“…pH 6 and that iron has a tendency to lower pH (Chaplin, 1984;Gaucheron et al, 1996;Balintova and Petrilakova, 2011).…”
Section: Experiments 2: Validation Of Inductively Coupled Plasma Mass mentioning
confidence: 99%
“…The addition of ferrous chloride (FeCl 2 ) to skim milk significantly decreased the pH of milk from 6.73 to 6.63. This, in turn, also displaces calcium and inorganic phosphate in the milk, which could potentially affect processes such as cheese making (Chaplin, 1984;Gaucheron et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation